THE INFLUENCE OF THE KANGAROO MOTHER CARE ON PHYSIOLOGICAL RESPONSES OF LOW BIRTH WEIGHT INFANTS: SYSTEMATIC REVIEWW - Alya Huwaida Anjani; Iis Aisyah; Popon Haryeti (Buletin Veteriner Udayana, 2024)
Low birth weight (LBW) babies are one of the causes of neonatal death. The inability of low birth weight babies to adapt to the environment will have an impact on the instability of the baby's physiological functions, such as increased heart rate, hypothermia, decreased respiratory frequency, and low oxygen saturation. Apart from using an incubator, one of the actions that is often recommended for LBW babies is Kangaroo Method Treatment (PMK). The aim of this study was to review and analyze previous research regarding the effect of kangaroo treatment on physiological responses in LBW. The method used in this research is a systematic literature review using 3 databases: Pubmed, Science Direct, and Google Scholar. This research has inclusion criteria, namely research articles with a maximum journal publication period of 7 years (2018-2024), articles using Indonesian and English, and availability of full text (Open Access Journal). After conducting the search, 1,240 articles were obtained, which were then selected again using the PRISMA abstract checklist, PRISMA checklist, and JBI critical appraisal checklist to obtain 12 articles. The kangaroo method can help low-birth-weight babies meet their needs by providing an environment and conditions similar to those of the mother's womb. This condition has an influence on low-birth-weight babies in the form of increasing body temperature, stability of the baby's breathing, increased pulse frequency, and baby saturation. The results of this systematic literature review show the influence of the kangaroo method of care on the physiological response of low-birth-weight babies. It is hoped that there will continue to be development and innovation in the implementation of the kangaroo method of care so that there is novelty and the problem of infant mortality throughout the country is currently decreasing.